Halogenated Dodecaborate Clusters as Agents to Trigger Release of Liposomal Contents. Issue 4 (12th January 2015) - Awad, Doaa; Bartok, Melinda; Mostaghimi, Farzin; Schrader, Imke; Sudumbrekar, Neeti; Schaffran, Tanja; Jenne, Carsten; Eriksson, Jonny; Winterhalter, Mathias; Fritz, Jürgen; Edwards, Katarina; Gabel, Detlef
Abstract Halogenated dodecaborates, and especially dodecaiodododecaborate(2−), are found to trigger effectively the release of the contents of phospholipid liposomes, including liposomes containing distearoylphosphatidylcholine and cholesterol, which are used clinically in cancer therapy. The basis of the release is studied through differential scanning calorimetry, cryo‐transmission electron microscopy, and atomic force microscopy. Upon administration at high concentrations, drastic morphological changes are induced by the dodecaborates. Their possible use in triggered release is suggested.